Pengaruh Masase Kaki Dan Aromaterapi Sereh Terhadap Penurunan Insomnia Pada LansiaDi Panti Wredha Daerah Surakarta - Al Azis, Wildan Fahad, Arina Maliya, S.kep.,Msi.,Med (2016)
Insomnia was disability to sleep despite of desire to do so. Elderly which experience risk of tsleep pattern trouble caused some factor like for example social pattern change, retired, couple live or close friend, medicine usage, disease which was in experiencing of elderly, trouble mood, anciety, trust to sleep, death, and feeling which were negative represent the happening of insomnia indicator. At insomnia handling could be done by farmakology therapy like antihistamin medicine owning side effects that was depends on will medicinize, elderly metabolism degradation, degradation of kidney function, and because the cognate function damage. While at non farmakology medication like citronella aromatherapy and foot massage have the excess overcome the insomnia without generating side effects. This research was purpose to identify the influence of foot massage and citronella aromatherapy to insomnia degradation at elderly. This research was using Quasy experiment design with pre and post test with control. Sample was used in this research counted 30 samples, consisted of 15 group control and 15 appropriate intervention group of criterion. This research was done in Pajang House of Surakarta and PMI Care House of Surakarta. The data analyze was used paired sample t-test and independent sample t-test. Pursuant to research result show there was influence of foot massage and citronella aromatherapy to insomnia degradation at elderly in Dharma Bhakti Pajang Retired House of Surakarta that was pre test group control with the experiment group have t count equal to 1,639 (p-value = 0,112). Post test experiment group and control group have t count equal to 3,919 (p-value = 0,001). Giving of foot massage therapy and citronella aromatherapy have effective in degrading insomnia level at elderly shown with paired sample t-test result that pre test and post test insomnia experiment group obtained t count equal to 7,544 (p-value = 0,000) pre test and post test insomnia control group obtained t count equal to 1,740 (p-value = 0,104).